THE VARIANT OF TYPE AND ABUNDANCE OF EPIPHELIC DIATOMS ON SAND SUBSTRATE IN BUNGUS COASTAL TELUK KABUNG WEST SUMATERA - Arwinda Novitri; Sofyan Ikhwan Siregar; Thamrin ' (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2016)
This research was conducted in February 2016 in the bungus coastal, Teluk Kabung. This aims of this research was to know the variant of type and abundance of epiphelic diatoms which saw from low tide activites (long soaked) and characteristic of the research location includes waters quality parameters and inform about waters domain ecology includes diversity, uniformity and dominance in around the bungus coastal, Teluk Kabung, West Sumatera. Data were obtained by direct observation, measurement and sampling in the field followed by identification of the type (species) of epiphelic diatoms at Marine Biological Laboratory, University of Riau. The results showed total epiphelic diatoms found were 12 species . That were Rhizosolenia sp, Guinardia sp, Triceratium sp, Melosira sp, Cerataulina sp, Hemiaulus sp, Dactyliosolen sp, Pseudo-nitzschia sp, Rhabdonema sp, Navicula sp, Cylindrotheca sp, dan Pleurosigma sp. The average abundance of diatoms based on zone each station highest was lower zone and lowest was upper zone. The value of diversity index (H’), uniformity index (E), and dominance index (D) show that the condition of research location has value which was in high diversity, organism uniformity wasn’t balance and no species dominated. Based on ANOVA test, concluded that abundance of epiphelic between each stasiun weren’t significant and abundance between each zone were significant.Keywords: Type and Abundance, Epiphelic Diatoms, Intertidal Zone, Teluk Kabung Bungus